Estrogen Receptor β as a Candidate Regulator of Sex Differences in the Maternal Immune Activation Model of ASD - Arnold, Madeline L.; Saijo, Kaoru (Frontiers in Molecular Neuroscience, 2021)
Interestingly, more males are diagnosed with autism spectrum disorder (ASD) than females, yet the mechanism behind this difference is unclear. Genes on the sex chromosomes and differential regulation by sex steroid hormones and their receptors are both candidate mechanisms to explain this sex-dependent phenotype. Nuclear receptors (NRs) are a large family of transcription factors, including sex hormone receptors, that mediate ligand-dependent transcription and may play key roles in sex-specific regulation of immunity and brain development. Infection during pregnancy is known to increase the probability of developing ASD in humans, and a mouse model of maternal immune activation (MIA), which is induced by injecting innate immune stimulants into pregnant wild-type mice, is commonly used to study ASD. Since this model successfully recaptures the behavioral phenotypes and male bias observed in ASD, we will discuss the potential role of sex steroid hormones and their receptors, especially focusing on estrogen receptor (ER)β, in MIA and how this signaling may modulate transcription and subsequent inflammation in myeloid-lineage cells to contribute to the etiology of this neurodevelopmental disorder.